Online Information through Publicity and The Consumers Perception The controversial case of Ryanair - trifu, alexandru (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
The online publicity/advertising is a form of promotion utilizing the internet as a quasi-exclusive mean of marketing, serving to attract new customers in larger numbers at costs as low as possible. The online advertising is considering actions by which the organization submits to general or specific audience information on its products and services, its brand names or more about itself. The online advertising success depends significantly on a solid knowledge of the advertising domain in general, on a good knowledge of internet as a medium of communication and prompt information, as well as on the consumer reaction and feedback As it is an area of utmost interest, where time equals money literally, the air transportation and especially the low-cost air transportation involves a need for a versatile and offensive online advertising.The case analyzed is paradoxical underlying perhaps the microeconomics principle of communicating vessels applicable to any system, but favorable to consumers (in this case). Even inconveniencies occurred (extra fees, more curious requirements regarding luggage, services on board), by overall, hence in a balanced situation, the possibilities to get sound and in a shorter time at destination, is more appreciated by the consumers (passengers). We speak about a psychological aspect in the relationship customer- service provider, meaning that the consumer retains the needed information, brand, even under the publicity form and becomes attached to the activity or service which brings him profit (tangible or not tangible).